2013
DOI: 10.1371/journal.pone.0071661
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Accelerates Pathogenesis of Murine Crohn’s Disease-Like Ileitis Independently of Obesity

Abstract: BackgroundObesity has been associated with a more severe disease course in inflammatory bowel disease (IBD) and epidemiological data identified dietary fats but not obesity as risk factors for the development of IBD. Crohn’s disease is one of the two major IBD phenotypes and mostly affects the terminal ileum. Despite recent observations that high fat diets (HFD) impair intestinal barrier functions and drive pathobiont selection relevant for chronic inflammation in the colon, mechanisms of high fat diets in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 34 publications
(32 reference statements)
5
76
0
Order By: Relevance
“…Inflammatory autoimmune arthritis jci.org Volume 125 Number 6 June 2015 matory state, with increased production of cytokines known to promote Th17 differentiation, including IL-1 and IL-6 (98). Moreover, mice placed on a high-fat diet demonstrate increased expression of IL-17, IL-23p19, and RORγt consistent with increased Th17 responses and have more rapid onset of colitis (99). Similarly, mice placed on a diet rich in trans fatty acids, which are found in processed hydrogenated vegetable oil, develop more severe intestinal inflammation in response to dextran sodium sulfate, and this is associated with an increase in both IL-17 and RORγt expression (100).…”
Section: Il-23 and Autoimmunitymentioning
confidence: 92%
“…Inflammatory autoimmune arthritis jci.org Volume 125 Number 6 June 2015 matory state, with increased production of cytokines known to promote Th17 differentiation, including IL-1 and IL-6 (98). Moreover, mice placed on a high-fat diet demonstrate increased expression of IL-17, IL-23p19, and RORγt consistent with increased Th17 responses and have more rapid onset of colitis (99). Similarly, mice placed on a diet rich in trans fatty acids, which are found in processed hydrogenated vegetable oil, develop more severe intestinal inflammation in response to dextran sodium sulfate, and this is associated with an increase in both IL-17 and RORγt expression (100).…”
Section: Il-23 and Autoimmunitymentioning
confidence: 92%
“…High-fat diets have been found to increase the severity of colitis that develops in mice 28, 29 . The essential fatty acids have been studied extensively in animal models of IBD.…”
Section: Nutrient-dependent Regulation Of Intestinal Inflammation In mentioning
confidence: 99%
“…A review conducted regarding patients suffering from Crohn disease (CD) 9 or ulcerative colitis (UC) concluded that high lipid intake increased the risk of inflammatory bowel diseases (3). Gruber et al (4) showed that high-fat diets (HFDs) intensified CD-like ileitis in TNF DARE/WT mice. Other studies revealed that a high-fat intake increased intestinal inflammation in a CD Multidrug resistance protein 1 a (Mdr1a) 2/2 mouse model (5) and aggravated UC induced by dextran sulfate sodium in mice (6).…”
Section: Introductionmentioning
confidence: 99%